Ultrasound-assisted tandem reaction of alkynes and trihaloisocyanuric acids by thiourea as catalyst in water. Issue 31 (3rd August 2017) - Zhang, Xingyu; Wu, Yundong; Zhang, Ya; Liu, Huilan; Xie, Ziyu; Fu, Shengmin; Liu, Fang
Abstract: With water as the sole solvent, a green and efficient method has been developed for the synthesis of various α, α-dihaloketones via ultrasound assisted p -tolylthiourea catalyzed tandem reaction of alkynes with trihaloisocyanuric acids. This synthetic route could effectively avoid the use of toxic organic solvents and transition metal catalysts, and the products could be obtained in a very short time at room temperature with good to excellent yields. Graphical abstract: